PRINCIPAL'S LEADERSHIP IN IMPROVING THE QUALITY OF EDUCATION - HATIDAH, Hatidah; Fitri Indriani, R.A Rodia; Harapan, Edi (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2024)
This study aims to determine school principals' leadership in improving education quality. This research uses a qualitative method. The subjects in this study are school principals, waka of facilities and infrastructure, waka of student affairs, teachers, and students. Interviews, observations, and documentation were carried out in data collection. The data is analyzed by data reduction, data presentation, and verification. The results of the study can be concluded that the leadership of the Principal includes aspects a) how to communicate, b) providing motivation, c) leadership ability, d) decision-making, and e) positive power is in an outstanding category. The quality aspect of education is based on Government Regulation Number 19 of 2005 concerning eight National Education Standards that have been implemented well.